Studi Tentang Sarana dan Prasarana Pendidikan Jasmani Terhadap Hasil Belajar Mata Pelajaran Pendidikan Jasmani Siswa Di Sekolah Menengah Pertama (Smp) Se-Kecamatan Adimulyo Kabupaten Kebumen Tahun Ajaran 2019/2020 - Wisnu Guntur Sutopo; Mohamad Saifudin Zuhri (Jurnal Kridatama Sains dan Teknologi, 2020)
This study aims to determine the state of infrastructure and physical education learning outcomes of junior high school students in Adimulyo District, Kebumen Regency. This research is a descriptive quantitative study with a survey method. The population of this study was 4 junior high schools in Adimulyo District, Kebumen Regency. From each school, researchers only took a sample of 10%. The sampling technique used in this study was random sampling. Based on a survey of physical education facilities and infrastructure survey of physical education learning outcomes of junior high school students in Adimulyo Subdistrict, Kebumen Regency, it was concluded that the average facilities and infrastructure that support the physical education learning process in Adimulyo Junior High School, namely in SMP N 1 Adimulyo 61% and in SMP N 2 Adimulyo 64% the ideal category to support the physical education learning process in accordance with the applicable curriculum. Whereas in the 23% Bhakti Praja Middle School category is less than ideal and in the Global IT Middle Nurul Istiqomah 15% the category is very less ideal to support the physical education learning process in accordance with the applicable curriculum. Physical education learning outcomes by looking at the student report card grades at SMP N 1 Adimulyo and at SMP N 2 Adimulyo have good report cards. This is evidenced from the collection of data about physical education learning outcomes of students who fall into either category with each having a percentage of 79% and 51%. While the report cards of students at SMP Bhakti Praja and SMP Global IT Nurul Istiqomah have pretty good report cards. This can be proven from the collection of data about physical education learning outcomes of students who fall into the quite good category with each having a percentage of 100% and 93%. Facilities and infrastructure are very influential on the learning outcomes of physical education students in junior high schools in the Adimulyo district, Kebumen district. Keywords: facilities and infrastructure, physical education, student learning outcomes, junior high school